Purification of the Recombinant Green Fluorescent Protein Using Aqueous Two-Phase System Composed of Recyclable CO2-Based Alkyl Carbamate Ionic Liquid - Song, Cher Pin; Liew, Poh En; Teh, Zora; Lim, Schian Pei; Show, Pau Loke; Ooi, Chien Wei (Frontiers in Chemistry, 2018)
The formation of aqueous two-phase system (ATPS) with the environmentally friendly and recyclable ionic liquid has been gaining popularity in the field of protein separation. In this study, the ATPSs comprising N,N-dimethylammonium N’,N’-dimethylcarbamate (DIMCARB) and thermo-responsive poly(propylene) glycol (PPG) were applied for the recovery of recombinant green fluorescent protein (GFP) derived from Escherichia coli. The partition behavior of GFP in the PPG + DIMCARB + water system was investigated systematically by varying the molecular weight of PPG and the total composition of ATPS. Overall, GFP was found to be preferentially partitioned to the hydrophilic DIMCARB-rich phase. An ATPS composed of 42% (w/w) PPG 1000 and 4.4% (w/w) DIMCARB gave the optimum performance in terms of GFP selectivity (1237) and yield (98.8%). The optimal system was also successfully scaled up by 50 times without compromising the purification performance. The bottom phase containing GFP was subjected to rotary evaporation of DIMCARB. The stability of GFP was not affected by the distillation of DIMCARB, and the DIMCARB was successfully recycled in three successive rounds of GFP purification. The potential of PPG + DIMCARB + water system as a sustainable protein purification tool is promising.